Progress in research on immunological mechanism of leprosy - Kosgei, Benson Kiprono; Yun-Peng, Luo (Asian Journal of Medical Sciences, 2015)
Leprosy is a chronic infection acquired after getting exposed to Mycobacterium leprae(M.Leprae), especially via contact or through nasal secretions of the affected hosts. 95% of the entire population is naturally immune to leprosy due to the inherent natural immunity against the pathogen. The components of M.leprae include the lipoarabinomannam, the mycolyl-arabinogalactan-peptidoglycan complex, the protein-peptidoglycan complex, and muramyl dipeptide which are potent inducers of inflammatory mediators, especially TNF-?. Immunologically and clinically leprosy is classified into the Tuberculoid pole, Borderline tuberculoid, Mid borderline, Borderline lepromatous and lepromatous pole. In the Tuberculoid pole, the naive CD 4 lymphocytes differentiate into either Th1 or Th17 cells. Th1 secretes IL-2, TNF-?, IFN-?, and Th17 secretes IL-17, IL- 21 and TNF-?. In the Lepromatous pole, the naive CD 4 lymphocytes differentiate into Th2 cells, which secrete IL-1?, IL-4, and IL-6 that promotes antibody formation. Knowing about the immune cells,mechanisms of their interaction and substances responsible in leprosy reactions can provide a potential way of enhancing the immune response to M.leprae especially in the Lepromatous pole or ways of preventing the nerve damage and skin lesions in leprosy. Asian Journal of Medical Sciences Vol.7(1) 2015 1-5